Análise comparativa entre os controladores fuzzy PD+I e PID convencional - Teixeira Junior, Carlos Alberto (Universidade Federal Rural do Semi-Árido, 2014)
Given the recent technological advances in the area of control engineering, advances many studies were performed to develop more precise and efficient controllers. According to the classical control theory, the main method currently used in process control is the Proportional Integrative Derivative controller (PID). Other technologies have also been developed to achieve similar results under other theoretical point of view. A specific tool that allows its application in process control is fuzzy logic. Besides allowing modeling in accordance with the PID controller, fuzzy logic also provides their use in nonlinear systems or in cases who do not admit mathematical modeling. Results obtained in academic studies that showed improvements in control systems, when the unification of classical control theory with fuzzy logic, there is a need to assess such effects. For this purpose, it is proposed mathematical modeling of a plant controlled by the level of a tank, in order to allow simulation and analysis from the point of view of the application of two different controllers: Fuzzy PD+I and the conventional PID. The results of this study demonstrated that the Fuzzy PD+I controller presented a satisfactory performance during the task of regulating the plant from standard input signals
Comparative analysis of the fuzzy controllers PD + I and conventional PID
Keywords: Fuzzy logic; Fuzzy control PD + I; PID control; Control Systems; Lógica fuzzy; Controle fuzzy PD+I; Controle PID; Sistemas de controle; ENGENHARIAS::ENGENHARIA ELETRICA